MENABUNG SAMPAH UNTUK MASA DEPAN PADA BANK SAMPAH PAPRIKA GRAHA INDAH PAMULANG - Benarda Benarda; Rakhmawati Oktavianna; Silvia Sari; Sevty Wahiddirani Saputri; Rini Septiowati (Abdimisi, 2019)
Community Service entitled Saving Waste for the Future at the Graha Indah Pamulang Paprika Waste Bank aims to provide knowledge about the importance of saving, providing savings training, inviting and instilling awareness to the actors of the garbage bank in Graha Indah Pamulang that the benefits from saving this rubbish for the future. The target of this service is all members of the garbage bank registered at the Graha Indah Pamulang Paprika Waste Bank. The results of this PKM proved that the members of the garbage bank Bambu Apus Village can master how to save well and increase the determination and concern for waste around the neighborhood.Keywords: Waste Bank, Saving, Future.